Optimization of a company’s property structure aiming at maximization of its profit using neural networks with the example of a set of construction companies - Rowland, Z.; Vrbka, J. (Математичне моделювання в економіці, 2016)
This contribution tries to find an efficient way of a company´s property optimization. It searches for such a property structure that would ensure adequate benefit, respectively, the appreciation of own capital provided for remuneration. To carry out the calculation balance sheets, respectively their parts informing about the company´s property are used, as well as income statements – the total taxed profit of all companies running their business in the CZ from 2006 to 2015. To find the model artificial neural networks are used – specifically a multi-layer perceptron network and a neural network of a radial basic function. The result is a neural structure that will help the building company find a suitable property structure, so that the company reaches the required ROE of 10% (a company is considered successful, if it reaches 10% and more on Return on Equity). The model is useful not only in company management but also in evaluating its performance and health by competitors, creditors or suppliers.